Hi Vincent!

In order to solve for x, we need to get x on one side of the equation. So, we can do that by subtracting 96 from both sides:

9 + 2x - 96 = x + 96 - 96 (will cancel out on the right side of the equation)

Next, compute 9 - 96 to decrease the amount of terms we have:

9 - 96 = -87, plug back into the equation:

2x - 87 = x

Next, subtract 2x from each side:

2x - 87 - 2x = x - 2x (will cancel out on the left side of the equation)

Combine terms:

-87 = -x (x - 2x = -x because the coefficient in front of x = 1 so 1 - 2 = -1)

Multiply by negative 1 on each side to obtain a positive number:

87 = x

You can plug 87 into each spot where the x is in the original problem to check your answer:

9 + (2*87) = 87 + 96

Let's solve for each side of the equation:

9 + (2*87) = 9 + 174 = 183

87 + 96 = 183

We have the right value for x!!

Let me know if you have any more questions!